2016
DOI: 10.1017/jfm.2015.703
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on the dynamics of an open triangle in a vertically oscillatory flow

Abstract: A direct-forcing fictitious domain method is employed to study the dynamics of an open triangle in a vertically oscillatory flow. The flow structures, the vertical force and the torque on the fixed body are analysed for the stable flow regime in which the flow structures form and evolve exactly in the same way in each period and the unstable regime, respectively. Our results indicate that in the stable flow regime for the body with upright orientation, the steady streaming structure mainly comprises two vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…From this figure, it is seen that the result of the present work and that of Shao et al. (2016) are generally in good agreement. Some discrepancies near the crests and troughs are probably caused by the effect of thickness.…”
Section: Figure 16supporting
confidence: 88%
See 3 more Smart Citations
“…From this figure, it is seen that the result of the present work and that of Shao et al. (2016) are generally in good agreement. Some discrepancies near the crests and troughs are probably caused by the effect of thickness.…”
Section: Figure 16supporting
confidence: 88%
“…The ranges for and in the current study are selected such that the two Reynolds numbers ( and ) are comparable to those in Shao et al. (2016), since the Navier–Stokes equations were also solved in their study. The ranges for other parameters in the two studies are also close.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the robotic flyer can maintain a stable body orientation during ascending, forward, and hovering flights. To some extent, this robotic flyer shared some similarities with the rigid or flexible objects which were able to hover in oscillating flows [14][15][16][17][18]. Although the promise of this design strategy has been demonstrated in test-flying the prototype, the underlying physical mechanisms which govern its locomotion capabilities are still not well understood.…”
Section: Introductionmentioning
confidence: 99%